Effects of Technology-Mediated Vocabulary Intervention for Third-Grade Students with Reading Difficulties. Issue 2 (2nd April 2020) - Fogarty, Melissa; Coyne, Michael D.; Simmons, Leslie E.; Simmons, Deborah C.; Henri, Maria; Kwok, Oi-Man; Ware, Sharon M.; Dalton, Kevin; Williams, Kimberly A.; Wang, Huan
Abstract: In this experimental study, we examined the effects of a technology-mediated intervention to improve students' understanding of academic vocabulary and its impact on measures of vocabulary and comprehension. The Vocabulators program was implemented in two states involving 24 teachers and 200 third-grade students identified as in need of supplemental vocabulary instruction. Individual students within each classroom were randomly assigned to treatment ( n = 100) or typical instructional practices ( n = 100) conditions. In the treatment condition, students received, on average, 29 lessons on vocabulary and comprehension. Results of linear regression analyses showed statistically significant and practical effects on experimenter-developed proximal measures of decoding (ES = 0.52), expressive vocabulary (ES = 0.78), receptive vocabulary (ES = 0.51), and near transfer measures of understanding vocabulary in sentences (ES = 0.65), and informational text comprehension (ES = 0.28). Group performance did not differ statistically on near transfer measures of sentence verification with vocabulary and narrative text comprehension as well as distal standardized measures of general vocabulary or reading comprehension. Findings suggest the potential impact of technology-based vocabulary/comprehension lessons to supplement typical instruction.